Numerical investigation of eccentrically loaded reinforced concrete sandwich walls - Haggag, May (AUC Knowledge Fountain, 2016)
Sandwich sections have a very complex nature due to variability of behavior of different materials within the section. Cracking, crushing and yielding capacity of constituent materials enforces high complexity of the section. Furthermore, slippage between the different layers adds to the section complex behavior. Conventional design guidelines address the design and construction of solid walls with little available information related to the behavior, design and construction of sandwich walls. Thus, an extensive study is needed to understand the behavior of the sandwich walls which leads to more use of such walls in construction industry in an effective and efficient manner. The purpose of the research presented in this thesis is to conduct numerical investigation of the structural behavior of sandwich walls under eccentric loading with range of eccentricity from 0.06 m to 0.43 m. The considered walls in the current investigation are composed of two reinforced concrete face layers and an insulating foam core layer. The two surface layers are connected to each other by reinforced concrete webs to act as shear connection media. ANSYS commercial software is used in the present study to model and analyze the walls. The reinforced concrete faces and webs are modeled using solid elements and the steel reinforcement is modeled using link elements. The analysis conducted herein is nonlinear static analysis incorporating geometric nonlinearity, cracking and crushing of concrete and yielding of steel. The model is validated by comparing its results to some of test results available in the literature. After validation, the model is used to perform extensive parametric study to investigate the effect of three key parameters on the axial force-bending moment interaction diagram of the walls. These parameters are the concrete compressive strength, reinforced concrete face thickness and number of shear connectors. Furthermore, for practical use of sandwich walls, a coefficient Î± is introduced in the present study that correlates the moment and axial load capacities of the sandwich wall to that of a corresponding solid wall of the same total thickness. The equation was developed using the parametric study data and regression analysis. The predicted Î± was used to construct the interaction diagram of the investigated wall and the results were compared with ANSYS results and showed good agreement.